Diagnosa Permasalahan Koneksi Internet Dengan Metode Backward Chaining - Fadli Fadilillah; Faisal Amir; Riyanto; Deddy Prayama; Fadhilah Oriyasmi (Politeknik Caltex Riau, 2022)
Problems Internet connection is an impact of interference experienced at important moments, where the impact can cause financial losses due to the delay in sending or uploading and downloading a file. Problems that occur on the internet include not being able to connect to the internet, slow internet connection, so that it cannot share files in the local network. And this is a factor that decreases performance results in any institution. This Expert System was built to diagnose internet connection problems, where this expert system uses the Backward Chaining Method, which is tracking backwards which starts reasoning from conclusions (goals), by searching for a set of hypotheses towards facts that support a set of hypotheses these. Backward Chaining Inference Engine, often called Object-Driven or Goal-Driven. If the premise clause matches the situation (TRUE value), the process will state the conclusion